The last kids on Earth and the skeleton road - Brallier, Max (Brallier, Max. Last kids on Earth, 2020)
Jack Sullivan and his friends go on a road trip to search for Thrull and his skeleton army equipped with the Midnight Blade and a crucial clue from June. Unfortunately while on their road trip, they are pursued by a the return of a monster they thought long dead and will have to come up with a plan to survive in order to save the world.